Stromal IL2 is related to the neutrophil/lymphocyte ratio in epithelial ovarian cancer - Santos, T.D.; Jammal, M.P.; Silveira, T.P.; Murta, E.F.C.; Nomelini, R.S. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
Introduction. There is a need for the development of new biomarkers for diagnosis and prognosis of ovarian cancer, which can ideally serve as targets for new therapeutic modalities and individualization of treatment. The objectives of this study were to determine the prognostic significance of the neutrophil/lymphocyte ratio in the peripheral blood of patients with ovarian cancer and tumor staging, and to associate this marker with the immune expression of a panel of cytokines. Methods. The study included 24 patients with malignant ovarian neoplasia treated at the Pelvic Mass Outpatient Clinic of the Clinical Hospital of the Federal University of Triângulo Mineiro. The neutrophil/lymphocyte ratio was calculated as the absolute number of neutrophils divided by the absolute number of lymphocytes. Expression of the cytokines was evaluated by the immunohistochemistry method (IL2, IL5, IL6, IL8, IL10 and TNF-R1). Fisher’s statistical test was used for the comparisons of immunohistochemical expression with the neutrophil/ lymphocyte ratio, and the unpaired T-Test was used in the analysis of the association of this ratio with tumor staging. Results. A neutrophil/lymphocyte ratio > 2.6 was significantly higher in the more advanced stages (II-IV) of malignant ovarian neoplasia (p = 0.0098). In addition, this ratio > 2.6 was associated with IL2 stromal immunostaining (1-3) (p = 0.0472). Conclusion. Stromal IL-2 is associated with higher a neutrophil/lymphocyte ratio, suggesting a worse prognosis in ovarian cancer and its role in tumor immunology; a neutrophil/lymphocyte ratio > 2.6 is associated with more advanced stages of malignant ovarian neoplasia.